Analytical determination of editions from bibliographic metadata - Ali Zeeshan Ijaz; Mikko Tolonen; Leo Lahti; Iiro Tiihonen (Oulun Yliopisto, 2022)
Analytical bibliography aims to understand the production of books. Systematic methods can be used to determine an overall view of the publication history. In this paper, we present the state of the art analytical approach towards the determination of editions using the ESTC meta data. The preliminary results illustrate that metadata cleanup and analysis can provide opportunities for edition determination. This would significantly help projects aiming to do large scale text mining.
Proceedings of the Research Data And Humanities (RDHUM) 2019 Conference: Data, Methods And Tools